P-Rex1 controls phagocytosis and the killing of bacteria by murine neutrophils independently of its catalytic activity - Islam, Priota; Chu, Julia Y.; Chetwynd, Stephen A.; Walker, Rachael; Hawkins, Phillip T.; Welch, Heidi C. E. (Frontiers in Immunology, 2025)
IntroductionP-Rex1 is a guanine-nucleotide factor for the small GTPase Rac (Rac-GEF) that is known to mediate neutrophil migration and ROS production in response to the activation of GPCRs. These roles of P-Rex1 are assumed to require its activation of Rac.MethodsHere, we used mice which lack P-Rex1 (Prex1–/–) and mice with catalytically inactive P-Rex1 (Prex1GD) to investigate the importance of the Rac-GEF activity in migration and ROS production. We also studied the requirement for P-Rex1 in degranulation, phagocytosis, NET formation, and the bactericidal activity of neutrophils.ResultsWe show that P-Rex1 mediates migration, ROS, and NETs through its Rac-GEF activity, but is dispensable for the degranulation of azurophil, specific and gelatinase granules. Surprisingly, P-Rex1 mediates the clearance of bacteria in vivo during septic peritonitis and the killing of bacteria by isolated neutrophils independently of its catalytic Rac-GEF activity. P-Rex1 also mediates the phagocytosis of IgG-opsonized zymosan yeast particles independently of its catalytic Rac-GEF activity. P-Rex1 is required for both integrin-dependent and Fc receptor-dependent phagocytosis, and it mediates the Fc receptor-dependent activation of Rac and Syk. Recently identified adaptor functions of P-Rex1 in GPCR trafficking and glucose uptake do not seem to underlie its GEF-activity independent roles in neutrophils.DiscussionTogether, our study identifies P-Rex1 as a regulator of NET formation and phagocytosis in neutrophils and reveals that P-Rex1 mediates bactericidal activity and phagocytosis independently of its catalytic Rac-GEF activity, through mechanisms not obviously linked to other recently identified adaptor functions.